STRATEGI PENGAMANAN SURAT RAHASIA BERBASIS SUMBER DAYA PERSURATAN - Sya’bany, Muhammad (Universitas Padjadjaran, 2015)
The meaning of secret mail in this research is to keep an organization or a team decision from the superior to the staffÂ in order hide and may not know by another person. Closed secret mail intend to success the organization activity, not make a riot at the public and not make a fail to protect organizationâs secret information. Secret information must be protect from interest people to take it away. The problem want to study is the thing about secret mailâs protectionbase on resources of correspondence at Education and Training Center for Mineral and Coal. The author will commitment the secret mailâs treatment with strategic simulation and observe how to create top secret. The research method used in this article is qualitative method with action research study. This research using the technique of prime data collection with observe, depth interview and document study. The author research: manage the secret mailâs facility, the manager of secret mail, and the process to close the secret mail. The researchâs result explain that secret mailâs equipment still not enough to protect secret mail such as there is no safes for the Memorandum of Understanding letter. Secret mail still get no perfect protection although that something easy to do such as laying the letter on the table. The integrity of secret mail management there is someone no realize that letter he/she made is the secret. The author can concluded that secret mail need safety action to protect it from other interest person.The protection that noticed secret mailâs means store for guarantee.Surat rahasia dalam penelitian ini adalah hasil keputusan suatu organisasi atau tim dari pimpinan kepada stafnya untuk dijaga agar isi informasi tersebut tersembunyi dan tidak boleh diketahui oleh orang lain. Informasi tertutup dimaksudkan suatu operasi tidak gagal, masyarakat tidak gaduh dan tidak gagal melindungi isisurat rahasia tersebut. Isi informasi rahasia dilindungi dari orang berkepentingan menguasai surat rahasia. Perumusan masalah yang diajukan adalah hal yang berkenaan mengenai hal pengamanan surat rahasia di Pusat Pendidikan dan Pelatihan Mineral dan Batubara. Metode penelitian yang digunakan di tulisan ini adalah metode kualitatif dengan menggunakan riset aksi. Penelitian menggunakan teknik pengumpulan data utama dengan observasi, wawancara mendalam dan studi dokumentasi. Penulis teliti mengenai tempat pengelola surat rahasia, pelaku pengelola surat dan aktivitas buat surat rahasia. Hasil penelitian menjelaskan sarana dan prasarana surat rahasia masih kurang melindungi surat rahasia seperti tidak ada brankas surat rahasia kerja sama. Pengamanan surat rahasia mendapatkan perlakuan kurang sempurna walau pengamanan tersebut hal yang mudah seperti meletakkan surat rahasia di atas meja. Integritas pengelola surat rahasia masih kurang seperti tidak tahu surat yang dibuatnya adalah rahasia. Penulis dapat simpulkan bahwa surat rahasia butuh tindakan yang aman untuk melindungi surat rahasia tidak dikuasai oleh orang yang berkepentingan.Â